Na(+), K(+), and Nonspecific Solute Requirements for Induction and Function of Galactose Active Transport in an Antarctic Psychrophilic Marine Bacterium - Hayasaka, Steven S. (1979)
An Antarctic psychrophilic marine Vibrio sp., with the inducible ability to accumulate non-metabolizable [(14)C]methyl-β-d-thiogalactoside through a galactose transport system, was isolated. Induction of [(14)C]methyl-β-d-thiogalactoside uptake was found to have a specific Na(+) requirement which was higher than that required for maximal uptake and growth. A specific K(+) requirement was found to be quantitatively the same for uptake, growth, and induction. At low suboptimal growth salinities in artificial seawater, growth, uptake, and induction were inhibited more by the generally low solute concentration than by a specific ion deficiency. Evidence was given that the effect of the nonspecific solute was not completely osmotic in nature. The nonspecific solute requirement was greatest for induction, followed by growth and substrate uptake.